2008
DOI: 10.1021/es7029625
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Polybrominated Diphenyl Ethers on Hand Wipes: Estimating Exposure from Hand-to-Mouth Contact

Abstract: Estimates of exposure to the flame-retardant polybrominated diphenyl ethers (PBDEs) in dust are very poor due to limited knowledge about dust ingestion. This study was undertaken to determine if PBDEs could be measured on hand wipes, and if so, to determine the distribution of levels present on the skin surface area to provide preliminary exposure estimates from hand-to-mouth contact. Hand wipes were collected from 33 individuals residing in the United States using sterile gauze pads soaked in isopropyl alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
169
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(179 citation statements)
references
References 38 publications
6
169
4
Order By: Relevance
“…Mouthing duration of hands, toys and non-dietary objects also decreased with age among the 1-12-year-old children. However, most current methods to estimate non-dietary ingestion incorporate frequency but not mouthing duration (Zartarian et al, 2000;Canales and Leckie, 2007;Nicas and Best, 2008;Stapleton et al, 2008;Tulve et al, 2010). It is likely with a longer mouthing duration that a greater surface area of the object or hand would be mouthed, which could lead to a greater amount of ingested contaminant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mouthing duration of hands, toys and non-dietary objects also decreased with age among the 1-12-year-old children. However, most current methods to estimate non-dietary ingestion incorporate frequency but not mouthing duration (Zartarian et al, 2000;Canales and Leckie, 2007;Nicas and Best, 2008;Stapleton et al, 2008;Tulve et al, 2010). It is likely with a longer mouthing duration that a greater surface area of the object or hand would be mouthed, which could lead to a greater amount of ingested contaminant.…”
Section: Discussionmentioning
confidence: 99%
“…Mouthing and hand contact frequencies are key parameters for estimating non-dietary ingestion and dermal exposure (Zartarian et al, 2006;Nicas and Best, 2008;Stapleton et al, 2008;Julian et al, 2009;Schleier et al, 2009;Macedo et al, 2010;Tulve et al, 2010), as well as soil/dust ingestion rates (Ö zkaynak et al, 2010) critical for most hazardous site clean-up risk assessments including Superfund sites (US EPA, 2004). Several studies have quantified these mouthing and hand contact behaviors in children (Zartarian et al, 1997aBrinkman et al, 1999;Reed et al, 1999;Freeman et al, 2001Freeman et al, , 2005Tulve et al, 2002;AuYeung et al, 2004;Black et al, 2005;Auyeung et al, 2006;Beamer et al, 2008); however, we know of only one other study that has reported any data on children over 6 years of age (Freeman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Better characterization of human dust ingestion rates constitutes a significant research gap. As it is thought dust ingestion occurs primarily via hand-to-mouth contact, a recently explored approach used contamination present in hand wipes to estimate exposure to PBDEs (86). However, uncertainties remain including the frequency and duration of hand-tomouth events and efficiency of hand-to-mouth transfer.…”
Section: Sources Of Variability In Concentrationsmentioning
confidence: 99%
“…Previous studies have shown that oral and dermal uptake of dust and soil, as well as ingestion of food are the main exposure pathways contributing to the total human exposure to PBDEs (Jones-Otazo et al, 2005;Harrad et al, 2008;Lorber, 2008;Stapleton et al, 2008;Fraser et al, 2009;Johnson-Restrepo and Kannan, 2009). The dust pathways tend to be more influential than food intake in North America (Jones-Otazo et al, 2005;Lorber, 2008), but not necessarily in Europe, where the food pathway can be dominant for tri-hexa-BDEs (Harrad et al, 2008).…”
Section: Introductionmentioning
confidence: 99%